A.c. and d.c. conduction processes in octakis[(4-tert-butylbenzylthio)-porphyrazinato]Cu(II) thin films with gold electrodes - Gül, Ahmet; Avciata, Ulvi; Altindal, Ahmet; Keski̇n, Bahadır (Springer Science and Business Media LLC, 2014)
The d.c. and a.c. electrical transport properties of Au/Pz/Au devices with various thickness of Pz(octakis((4-tert-butylbenzylthio)-porphyrazinato)Cu(II)) layer have been investigated. Measurements revealed that, in contrast to previously investigated Au/Pc/Au structures, low voltage d.c. behaviour of the films can be described by the field-lowering mechanisms with a log(J) ∝ V 1/2 current density-voltage charac- teristics under forward and reverse bias. For high reverse voltages, the observed ln(J/V 2 ) - 1/V characteristics indicated that the origin of conduction mechanism is Fowler-Nordheim tunnelling (FNT). On the other hand, the voltage dependence of current density at the higher forward-voltage region indicates that the mechanism of conduction in Au/Pz/Au devices is space charge limited conduction dominated by exponential trap distribu- tion. A thickness independent barrier height was observed for tunnelling, while the total trap concentration show a general tendency to decrease with increasing film thickness. The a.c. conductivity showed two regions in the ln(σa.c.) - ln( f ) plots having different slopes, leading to the conclusion that for low frequency region, the dominant conduction mechanism is a small polaron tunnelling at all temperatures, whereas for high frequency region, correlated barrier hopping model is the dominant mechanism in the investigated devices.